The implications of stakeholder consultation on employee engagement: An African cross-border acquisition - van Niekerk, Annelize (Frontiers in Psychology, 2022)
The purpose of the study was to explore the power of stakeholder consultation on employee engagement during a cross-border acquisition in a multi-cultural context. Further, to describe the psychosocial factors at play during the employee involvement process towards enhancing employee engagement. This qualitative study presents the results from data collected in Tanzania through semi-structured interviews (46 participants) and analyzed in accordance with Tesch’s content analysis method. The results of this study contribute to the body of knowledge to better understand the psychosocial factors at play within a multi-cultural environment which inform stakeholder consultation and will enable or hinder employee engagement. A transitional space should be created, fostering mature stakeholder engagement, promoting employee inclusion, engagement, and knowledge sharing. Bringing together two worlds requires building bridges to cross the cliff between contexts and overcoming diversity challenges, while incorporating diversity management in the consulting process. A multi-cultural team should be established, incorporating diversity management, applying the principles of respect, participation and transparent communication, with regular feedback on decisions made. External stakeholders in authoritative positions are not well received and should consider traditional superiority versus business hierarchy when establishing leader-follower relationships.